Detection of glutathione S-transferases M1, T1 gene deletions among cancer patients in Mongolia - Janchiv, Temuujin; Dorj, Enkhgerel; Baldorj, Ochirkhuyag; Janchiv, Khulan (Proceedings of the Mongolian Academy of Sciences, 2020)
Various types of toxic xenobiotic and electrophilic compounds, which were formed from the glutathione S-transferases cell metabolism and the oxidation stress, are the group enzymes with detoxification roles that are involved in the metabolism phase II. During the GSTM1 and GSTT1 gene homozygous deletion, the above enzymes completely lose their activity and consequently somatic mutation is formed. Furthermore, it is considered that it might have increased the risk of cancer. Therefore, the research works which connected the GSTMI and GSTTI gene deletion with the cancer of kidney, lung, prostate, breast, stomach, esophagus, large and narrow intestines. In this study, two gene deletion distribution is detected for cancer patients. We collected the blood samples of 60 patients who have been diagnosed with cancer. The DNA was extracted and the GSTM1 and GSTT1 genes were amplified using multiplex PCR. According to our research, the above two gene deletion is predominant among patients who have cancer. The results showed that from the total 60 patients GSTM1 and GSTT1 both deletions, GSTM1 gene deletion - 35%, GSTM1 gene deletion - 25%, GSTT1 gene deletion - 26.7%, GSTM1 and GSTT1 both positive -13.3 %. Therefore, we think that in order to prevent tumor and cancer, these gene mutations must be revealed and it is important to bring the risky group under medical control and assist them in order to prevent them from this disease.